CDS calibration under an extended JDCEV model. Issue 9 (2nd September 2019) - Di Francesco, Marco; Diop, Sidy; Pascucci, Andrea
ABSTRACT: We propose a new methodology for the calibration of a hybrid credit-equity model to credit default swap (CDS) spreads and survival probabilities. We consider an extended Jump to Default Constant Elasticity of Variance model incorporating stochastic and possibly negative interest rates. Our approach is based on a perturbation technique that provides an explicit asymptotic expansion of the CDS spreads. The robustness and efficiency of the method is confirmed by several calibration tests on real market data.